Kontribusi dan Kekhasan Pemikiran Pendidikan Sunan Bonang dalam perspektif Pendidikan Islam Modern - Sani, Mutiara; Khamdani, Agus Walid; Mujib, Ahmad; Khoir, Mulyanto Abdullah (TSAQOFAH, 2025)
Sunan Bonang was a central figure in the spread of Islam in 15th-century Java, known not only as a preacher but also as a visionary educator with a contextual and sufistic approach. This study aims to examine the contributions and distinctive features of Sunan Bonang’s educational thought in relation to the principles of modern Islamic education. Utilizing a descriptive qualitative approach, the research explores Sunan Bonang’s educational ideas and practices through historical and contextual analysis, emphasizing the integration of local culture, arts, and tasawuf teachings. The findings reveal that Sunan Bonang developed an educational method that combined sufistic values with local artistic expressions, such as the use of tembang Jawa as a medium for dakwah and character formation. This strategy reflects a holistic, cultural, and value-based Islamic educational approach. The study concludes that Sunan Bonang’s educational thought holds significant relevance for the development of contemporary Islamic education models that honor local wisdom and foster spiritual character.